إقليم وادي سوف بالجنوب الشرقي الجزائري، المجال والساكنة 1900 ـ 1962م - عثماني, الجباري (University of Eloued جامعة الوادي, 2022)
إقليم وادي سوف متميز بخصائصه الجغرافية والبشرية والعمرانية، وهو ضمن الأقاليم الصحراوية التي تدخل ضمن حيز الجنوب الشرقي الجزائري، وصفه أحد الكتاب الفرنسيين بالجمهورية الصغيرة، بحيث يحتل موقعا جيوسياسيا متفردا؛ جعله قبل الغزو الفرنسي، محط أنظار بايات تونس المجاورة شرقا، وسلاطين بني جلاب غربا، وأجواد مشايخ العرب الزيبانية شاملا. ونهدف من خلال هذه المداخلة أن نجلي للقارئ الكريم طوبونيميا المُسمى، والمجال الجغرافي للإقليم، وأثر البيئة الصحراوية القاسية على ساكنة المنطقة. كما نتعرف على النسيج الاجتماعي والتركيبة القبلية لمجتمع الوادي. Abstract: Oued Souf is characterized by its geographical and human characteristics, and is among the desert regions that enter the south-east of Algeria, described by one French writer as a small republic, occupying a unique geopolitical position, which made it before the French invasion; Through this contribution, we aim to identify the origin of the territory's designation, the geographical space of the territory and the impact of the harsh desert environment on the population of the region. We learn about the social fabric and tribal composition of the valley community.
Oued Souf Region, South East Algeria, Geography, Population 1900-1962 AD
مداخلة
Keywords: الوادي؛ سوف؛ السكان؛ الاستعمار؛ الجنوب الشرقي; El-Oued; Souf; The population; Colonialism; South-east.